ANALISIS KEBIJAKAN AKUNTANSI DALAM PERATAAN LABA (Studi Kasus di Hotel X Solo) - Fadjar Harimurti, Asep Vidianto, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
This research aims to determine wheter there is income smoothing practices in hotel X Solo, in what way do income smoothing practices and the impact arising from the practice of income smoothing. This research use observation and documentation method. The focus of this research is the revenue and expenditure transaction in which researchers examined the accounting records and view documents in the revenue cycle expenses. Furthermore, researchers examine in more detail the gaps that may be an opportunity in the management of income smoothing. The result of this research indicate that in 2015 the hotel X Solo conduct income smoothing practices by using the accounting method wherein hotel X Solo management fees break down several accounts in one period into the next period, causing inauthenticity financial statements. Of income smoothing practices that raised the impact that researchers found in the research, that there errors in decision making budgeting for the next year, because the revenue and cost budgeting process hotel X Solo for the following year refers to the achievement of revenue and expenditures from the previous year.Keywords: Income smoothing, income smoothing method